Ontologie der Vermögen (powers) und Dispositionen - Runggaldier, Edmund (Zeitschrift für katholische Theologie, 2011)
Naturalism is – even in its modern, differentiated forms – inherently opposed to a Christian concept of human persons. After concluding two research projects on the aspects of diachronic persistence of human persons the Department of Christian Philosophy at the University of Innsbruck has just inaugurated a new research project on »Powers and the Identity of Agents« in order to deepen and further the results already achieved. This article lays out the questions and problems to be dealt with as they emerge from the earlier research projects.